IDENTIFICATION AND INDIVIDUALIZATION OF A NATURAL PERSON IN THE INTERNET COMPUTER NETWORK: LEGAL ASPECTS - Yevgen Michurin (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2022)
Introduction. Legal regulation of individualization on the Internet is being formed. The practice of individualization of individuals on the Internet is mainly dispositive. In some cases, it is necessary to coordinate the name of an individual and his NickName. In particular, for public services, distance learning, smart contracts. Therefore, it is necessary to investigate the legal nature of individualization of an individual on the Internet. The relevance of such research is increasing with the development of the Internet and its legal regulation.